Photosensitized electron transfer processes in SiO(2) colloids and sodium lauryl sulfate micellar systems: Correlation of quantum yields with interfacial surface potentials - Laane, Colja (1981)
The effectiveness of negatively charged colloidal SiO(2) particles in controlling photosensitized electron transfer reactions has been studied and compared with that of the negatively charged sodium lauryl sulfate (NaLauSO(4)) micellar system. In particular, the photosensitized reduction of the zwitterionic electron acceptor propylviologen sulfonate (PVS(0)) with tris(2,2′-bipyridinium)ruthenium(II) [Ru(bipy)(3)(2+)] as the sensitizer and triethanolamine as the electron donor is found to have a quantum yield of 0.033 for formation of the radical anion (PVS([unk])) in the SiO(2) colloid compared with 0.005 in the homogeneous system and 0.0086 in a NaLauSO(4) micellar solution. The higher quantum yields obtained with the SiO(2) colloidal system are attributed to substantial stabilization against back reaction of the intermediate photoproducts—i.e., Ru(bipy)(3)(3+) and PVS([unk])—by electrostatic repulsion of the reduced electron acceptor from the negatively charged particle surface. The binding properties of the SiO(2) particles and NaLauSO(4) micelles were investigated by flow dialysis. The results show that the sensitizer binds to both interfaces and that the SiO(2) interface is characterized by a much higher surface potential than the micellar interface (≈-170 mV vs. -85 mV). The effect of ionic strength on the surface potential was estimated from the Gouy-Chapman theory, and the measured quantum yields of photosensitized electron transfer were correlated with surface potential at different ionic strengths. This correlation shows that the quantum yield is not affected by surface potentials smaller than ≈-40 mV. At larger potentials, the quantum yield increases rapidly. The quantum yield obtained in the micellar system at different strengths fits nicely on the correlation curve for the colloid SiO(2) system. These results indicate that the surface potential is the dominant factor in the quantum yield improvement for PVS(0) reduction.